Zasady weryfikacji i zatwierdzania taryf za zbiorowe zaopatrzenie w wodę i zbiorowe odprowadzanie ścieków – zarys problematyki - Ciszewski, Łukasz (Wydawnictwo Naukowe UAM, 2014)
The necessity of guaranteed water supply and quality service underlay a legislative decision made to ensure an administrative supervision of that activity. One of the basic instrument s of the control is a procedure of handling a tariff of water and sewage rates and charges. Pursuant to the Act of 7 June 2001 on water supply and sewerage treatment service, the revision and approval of tariffs has been vested in individual municipalities, and the regulations governing their activity have practically remained intact since the implementation of the Act, notwithstanding the many problems and doubts that have been arising as to the functioning of public administration organs, administrative courts, or the operations of companies. The paper presents issues related to the revision and approval of tariffs. The key issues that have been analysed include the defi nition of a tariff and a tariff application, establishing the legal nature of such documents, and the identifi cation of the principles as well as limits of tariff revision performed by a municipality executive body in the process of tariff approval. It also contains de lege ferenda conclusions which point to the need to replace municipality bodies involved in the process with specialised central or regional organs, to ensure participation of a professional and independent regulator, free from the pressures of local politics (maintaining, of course, the ex ante supervision).
Principles of revising and approving water and sewerage tariffs – outline of the issue
Keywords: tariff; tariff application; tariff approval; tariff revision; water and sewage enterprise